A method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst

By combining high-temperature pyrolysis and chemical etching with ball milling method and template method, a graded pore high-entropy metal-nitrogen doped carbon catalyst was prepared, which solved the problem of preparation of high-entropy metal single-atom catalysts in the prior art, and achieved efficient coordinated catalysis of the catalyst performance.

CN116020515BActive Publication Date: 2025-01-17HEBEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310069852.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-07
Publication Date
2025-01-17
Estimated Expiration
2043-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare high-entropy metal single-atom catalysts, especially high-entropy metal-nitrogen doped carbon catalysts with graded pore structures, limiting the mass transfer efficiency and catalytic performance of the catalytic process.

Method used

The SiO2@ high-entropy ZIFs composite was prepared by using ball milling method and template method combined with high-temperature pyrolysis and chemical etching to form a graded pore high-entropy metal-nitrogen doped carbon catalyst, breaking the thermodynamic limitations and realizing the high-entropy metal position. synergy of points.

Benefits of technology

The formation of the hierarchical pore structure is achieved, the active site exposure and mass transfer efficiency of the catalyst is improved, the synergistic catalytic capacity is enhanced, and excellent catalytic performance is demonstrated, such as the high conversion and selectivity of styrene epoxidation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116020515B_ABST
    Figure CN116020515B_ABST
Patent Text Reader

Abstract

The present invention is a method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst. The method comprises the following steps: (1) placing reactants, SiO2 microspheres and grinding balls in a ball mill, washing with ethanol, and vacuum drying to obtain a SiO2@high entropy ZIFs complex; (2) placing the SiO2@high entropy ZIFs complex obtained in the previous step in a quartz boat, maintaining it at 800-1100°C for 1-3h, then soaking it with acid or alkali to remove the SiO2 template, and washing it with ethanol and vacuum drying to obtain a hierarchical pore high entropy metal-nitrogen doped carbon catalyst. The present invention has great potential application value in the fields of photothermal catalysis and synergistic catalysis, and broadens its application in the field of catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical solution of the present invention relates to the technical field of metal single-atom catalyst preparation, and specifically to a method for preparing a hierarchical pore high-entropy metal-nitrogen-doped carbon catalyst. Background Art

[0002] Since the concept of "Single-Atom Catalysts" (SACs) was jointly proposed by Zhang Tao's team from Dalian Institute of Chemical Physics, Professor Li Jun from Tsinghua University, and Professor Liu Jingyue from Arizona State University in 2011, SACs have quickly become the research frontier in the field of heterogeneous catalysis, and are expected to become an ideal catalyst to bridge the gap between homogeneous catalysts and heterogeneous catalysts. SACs are the ideal state of supported metal catalysts, achieving high utilization of metal atoms while having the advantages of "isolated sites" of homogeneous catalysts, structural stability, and easy separation of heterogeneous catalysts (Nat.Chem.2011,3,634-641). The metals in SACs are uniformly distributed on the carrier in the form of single atoms. The uniformly dispersed single atoms as catalytic active centers are similar to homogeneous catalysis, achieving high activity and high selectivity of catalytic reactions, and also providing new solutions for the study of catalyst mechanisms. (Nat.Rev.Chem.2018,2,65-81)

[0003] Zeolitic imidazolate frameworks (ZIFs) are a subclass of metal organic frameworks (MOFs) materials. Due to their intrinsic physical and chemical properties such as orderly distributed metal nodes, high nitrogen content and clear pore structure, they are an ideal precursor for preparing SACs. By regulating the pyrolysis temperature, holding time and atmosphere, various metal SACs (Mn, Fe, Co, Ni, Cu, Zn, etc.) can be prepared using ZIFs as precursors. However, most of the ZIFs-derived SACs reported so far are mainly microporous (<2nm) structures, and single atomic sites are embedded in the material, which severely limits the mass transfer efficiency and accessibility of metal active sites during the catalytic process. Preparing ZIFs-derived SACs into ordered macroporous structures is considered to be an effective way to solve the above problems (Science 2018, 359206-210). The ordered macroporous structure can not only expose internal active sites and improve mass transfer efficiency, but also is an important way to expand the catalytic application of this type of material involving large-sized compounds (Chem. Eng. J. 2022, 429 132150).

[0004] In addition, due to thermodynamic limitations, ZIFs-derived SACs can only realize SACs containing one or two metal single-atom sites, which makes it only able to catalyze reactions with relatively simple mechanisms and lack synergistic catalytic ability (Angew.Chem.Int.Ed.2019,58,5018-5022). As a new type of material system, high-entropy materials (solid solutions or homogeneous structures formed by equiatomic ratios of five or more elements) have attracted widespread attention from researchers in recent years. The coordination of multiple main components shows new properties and performances that traditional materials do not have. In high-entropy SACs catalysis, the synergistic effect between multi-metal sites makes it have catalytic performance far superior to that of single metal catalysts (Chem Catal.2,1624-1656). However, the current process for preparing high-entropy SACs is relatively cumbersome and mainly based on microporous structures. Therefore, it is of great research significance to develop a convenient and universal new method to prepare a hierarchical pore (macroporous-microporous) high-entropy metal-nitrogen-doped carbon. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst in view of the deficiencies in the current technology. The method combines ball milling and template method to prepare SiO2@high entropy ZIFs complex, wherein the ball milling method corresponds to high entropy metal, the template method corresponds to hierarchical pores (macroporous-microporous), and the SiO2 microspheres act as hard templates during the ball milling process. Then, a hierarchical pore high entropy metal-nitrogen doped carbon catalyst is prepared by high temperature pyrolysis and chemical etching. The present invention has great potential application value in the fields of photothermal catalysis and synergistic catalysis, and broadens its application in the field of catalysis.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst, the method comprising the following steps:

[0008] 1) Preparation of SiO2@High Entropy ZIFs Composites by Ball Milling

[0009] The reactants, SiO2 microspheres and grinding balls are placed in a ball mill and ball milled for 1-10 hours to obtain a mixture containing a SiO2@high entropy ZIFs complex; finally, the mixture is washed with ethanol for 3-5 times, and vacuum dried at 70-100°C to obtain a SiO2@high entropy ZIFs complex;

[0010] The reactants are 2-methylimidazole, a zinc-containing compound and a mixed metal salt; the mass of SiO2 microspheres corresponding to 1g of the reactants is 0.05-5g; the total molar amount of the mixed metal salt and the zinc-containing compound corresponding to 1mol of 2-methylimidazole is 0.02-1mol, and the molar ratio of the mixed metal salt to the zinc-containing compound is 1:1-20;

[0011] The mixed metal salt is any five or all six metal salts of iron salt, cobalt salt, nickel salt, copper salt, manganese salt and cerium salt, and the molar ratio of each metal salt is 1:1;

[0012] The diameter of the grinding balls is 0.4 cm to 1.0 cm; the number of grinding balls corresponding to 1 g of reactant is 2 to 30; the speed of the ball mill is 300-3000 r / min;

[0013] The particle size of the SiO2 microspheres is 100-1000nm.

[0014] The iron salt is: Fe(NO3)3·9H2O, Fe(NO3)3, Fe2(SO4)3 or Fe(OH)(CH3COO)2;

[0015] Cobalt salts are: Co(NO3)2·6H2O, Co(NO3)2, CoSO4 or Co(CH3COO)2;

[0016] Nickel salts are: Ni(NO3)2·6H2O, Ni(NO3)2, NiSO4 or Ni(CH3COO)2;

[0017] Copper salts are: Cu(NO3)2·3H2O, Cu(NO3)2, CuSO4 or Cu(CH3COO)2·H2O;

[0018] Manganese salts are: Mn(NO3)2·4H2O, Mn(NO3)2, MnSO4 or Mn(CH3COO)2·4H2O;

[0019] Cerium salt is: Ce(NO3)3·6H2O, CeCl3, Ce(SO4)2 or CeCl3·H2O;

[0020] The zinc-containing compound is Zn(OH)2, ZnO, Zn(NO3)2·6H2O or Zn(NO3)2.

[0021] 2) Preparation of hierarchical pore high entropy metal-nitrogen doped carbon catalyst

[0022] The SiO2@ high entropy ZIFs composite obtained in the previous step was placed in a quartz boat and heated in a tube furnace at 2-5 °C min -1 The temperature was raised from room temperature to 800-1100°C and maintained for 1-3 hours, and then cooled naturally to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composite. The SiO2 template was removed by soaking in acid or alkali for 1-4 days, and then washed with ethanol for 3-5 times. After vacuum drying at 70-100°C, a hierarchical pore high entropy metal-nitrogen doped carbon catalyst was obtained.

[0023] The acid is hydrofluoric acid with a mass fraction of 10-40%, and the alkali is a sodium hydroxide solution with a mass fraction of 0.5 mol / L-2 mol / L.

[0024] The essential features of the present invention are:

[0025] Traditional methods for preparing single-atom catalysts are mostly solution methods (requires the addition of solvents), and it is difficult to obtain high-entropy single-atom catalysts due to thermodynamics. The present invention cleverly combines ball milling (breaking thermodynamic limitations), template method (forming macropores) and pyrolysis method to prepare hierarchical pore high-entropy metal-nitrogen-doped carbon catalysts in a simple and convenient way.

[0026] The beneficial effects of the present invention are:

[0027] (1) The present invention provides a convenient method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst. Figure 1 It can be seen that the prepared SiO2@ high entropy ZIFs composite has an obvious crystal structure. Figures 2 to 4 It can be seen that the prepared hierarchical high-entropy metal-nitrogen doped carbon has both macropores and micropores. Compared with the traditional ZIFs-derived single-atom catalysts with mainly micron structures, hierarchical pores can not only expose internal active sites and improve mass transfer efficiency, but also are an important way to expand the catalytic application of such materials involving large-sized compounds. The performance, structure and preparation ideas of the material are novel and have not been reported in the literature.

[0028] (2) The present invention proposes a method for preparing hierarchical high-entropy metal-nitrogen-doped carbon catalysts by combining ball milling, template method and pyrolysis method. Compared with the traditional solution method, the ball milling process does not require the use of organic solvents and the mechanochemical reaction is conducive to the formation of high-entropy ZIFs. The preparation method is novel and the process is simple and easy. Figures 5-6 It can be seen that the prepared hierarchical high-entropy metal-nitrogen doped carbon has five metal single atoms and their nanoparticles at the same time. The high-entropy metal sites can not only increase the active sites, but also promote the synergistic catalytic ability, thereby improving the catalytic efficiency. Figure 7 It can be seen that the prepared hierarchical pore high entropy metal-nitrogen doped carbon catalyst uses O2 as the only oxidant to show excellent catalytic performance for the epoxidation reaction of styrene (conversion rate: 96%; selectivity: 90%). Therefore, the prepared hierarchical pore high entropy metal-nitrogen doped carbon has excellent catalytic performance, is easy to achieve large-scale and industrialized production when used, and has good industrial development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the XRD diffraction pattern of the SiO2@high entropy ZIFs composite in Example 1;

[0030] Figure 2is the N2 adsorption-desorption isotherm of the hierarchical pore high entropy metal-nitrogen-doped carbon catalyst in Example 1;

[0031] Figure 3 This is a SEM photo of the hierarchical pore high entropy metal-nitrogen doped carbon catalyst in Example 1;

[0032] Figure 4 This is a TEM image of the hierarchical pore high entropy metal-nitrogen doped carbon catalyst in Example 1;

[0033] Figure 5 This is a HAADF-STEM image of the hierarchical pore high entropy metal-nitrogen doped carbon catalyst in Example 1;

[0034] Figure 6 Element mapping diagram of the hierarchical pore high entropy metal-nitrogen doped carbon catalyst in Example 1;

[0035] Figure 7 This is the NMR spectrum of the solution before and after the epoxidation reaction of styrene catalyzed by the hierarchical pore high entropy metal-nitrogen-doped carbon catalyst in Example 1. DETAILED DESCRIPTION

[0036] The preparation process of the present invention is as follows: (1) using 2-methylimidazole, mixed metal salts, and zinc-containing compounds as precursors and SiO2 microspheres as templates, a SiO2@high-entropy ZIFs complex is prepared by ball milling; (2) a hierarchical pore high-entropy metal-nitrogen-doped carbon catalyst is obtained by high-temperature pyrolysis and chemical etching.

[0037] The preparation process of the present invention is simple and easy to prepare on a large scale. The obtained product has excellent photothermal conversion performance and highly active multifunctional sites. The hierarchical pore structure can easily expose more internal active sites and improve mass transfer efficiency. High-entropy metal single atoms and nanoparticles are conducive to increasing synergistic catalytic ability. These characteristics make it have huge potential application value in the fields of tandem catalysis and synergistic catalysis.

[0038] The mixed metal salts include iron salts: Fe(NO3)3·9H2O, Fe(NO3)3, Fe2(SO4)3, Fe(OH)(CH3COO)2; cobalt salts: Co(NO3)2·6H2O, Co(NO3)2, CoSO4, Co(CH3COO)2; nickel salts: Ni(NO3)2·6H2O, Ni(NO3)2, NiSO4, Ni(CH3COO)2; copper salts: Cu(NO3)2·3H2O, Cu(NO3)2, CuSO4, Cu(CH3COO)2·H2O; manganese salts: Mn(NO3)2·4H2O, Mn(NO3)2, MnSO4, Mn(CH3COO)2·4H2O; cerium salts: Ce(NO3)3·6H2O, CeCl3, Ce(SO4)2, CeCl3·H2O; zinc-containing compounds Zn(OH)2, ZnO, Zn(NO3)2·6H2O, Zn(NO3)2 are well-known materials.

[0039] Embodiment 1:

[0040] (1) Add 0.06 mol of 2-methylimidazole (4.93 g), 0.6 mmol of Ni(NO3)2·6H2O (0.17

[0041] g), 0.6mmol Fe(NO3)3·9H2O(0.24g), 0.6mmol Co(NO3)2·6H2O(0.17g), 0.6mmol Mn(NO3)2·4H2O(0.15g), 0.6mmol Ce(NO3)3·6H2O(0.26g), 0.012mol Zn(NO3)2·6H2O(3.57g), 1g SiO2 microspheres (particle size 250nm) and 35 grinding balls (diameter 0.5cm), ball milled at a speed of 1000r / min for 3h, where the total mass of the reactants was 9.49g. Finally, the mixture was washed 3 times with ethanol and dried in vacuum at 100℃ to obtain SiO2@high entropy ZIFs complex. (After calculation, the total molar amount of the mixed metal salt and the zinc-containing compound corresponding to each 0.06 mol of 2-methylimidazole is 0.015 mol; the zinc-containing compound is 0.012 mol, the mixed metal salt is 0.003 mol, and the reactant is 9.49 g)

[0042] Figure 1 The crystal structure of the SiO2@high entropy ZIFs complex was characterized using a D8-Davinci X-ray powder diffractometer. From the figure, it can be concluded that the SiO2@high entropy ZIFs complex has obvious ZIFs diffraction peaks, indicating that the high entropy ZIFs single crystal was successfully formed.

[0043] (2) The obtained SiO2@high entropy ZIFs composite was placed in a quartz boat and heated in a tube furnace at 5°C min -1 The temperature was raised from room temperature to 1000°C for 3 hours, and then naturally cooled to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composites. The composites were soaked in 10% hydrofluoric acid for 1 day, washed with ethanol for 3 times, and dried in vacuum at 100°C to obtain hierarchical pore high entropy metal-nitrogen doped carbon.

[0044] Figure 2 The pore structure of the hierarchical pore high entropy metal-nitrogen doped carbon was characterized using a Micromeritics ASAP 2020M+C specific surface area and porosity analyzer. From the figure, it can be concluded that the hierarchical pore high entropy metal-nitrogen doped carbon has microporous and mesoporous structures.

[0045] Figure 3 This is a SEM photo of hierarchical high entropy metal-nitrogen doped carbon obtained by scanning the hierarchical high entropy metal-nitrogen doped carbon using a FEI Nano SEM 450 scanning electron microscope. From the figure, it can be seen that the material presents a macroporous structure. In addition, the formation of metal nanoparticles (white particles) can also be seen from the figure.

[0046] Figure 4 This is a TEM photo of hierarchical pore high entropy metal-nitrogen doped carbon obtained by using a FEI Talos F200S transmission electron microscope. From the picture, it can be seen that the material presents a macroporous structure, and the metal nanoparticles are on the macroporous structure framework (black particles).

[0047] Figure 5 This is a spherical aberration corrected HAADF-STEM photo obtained by characterizing graded pore high entropy metal-nitrogen doped carbon using a Titan Themis Cubed G2 60-300 spherical aberration corrected transmission electron microscope. It can be seen from the figure that the metal atoms exist in the form of single atomic dispersion.

[0048] Figure 6 This is an element mapping photo obtained by characterizing the hierarchical pore high entropy metal-nitrogen doped carbon using a FEI Talos F200S transmission electron microscope. From the photo, it can be seen that the high entropy metal sites are evenly distributed in the macroporous structure.

[0049] Figure 7This is the nuclear magnetic spectrum of the solution before and after the hierarchical pore high entropy metal-nitrogen-doped carbon catalyst catalyzed the epoxidation reaction of styrene using a Bruker 400 nuclear magnetic resonance (NMR) test. From the figure, it can be seen that the prepared hierarchical pore high entropy metal-nitrogen-doped carbon catalyst shows excellent catalytic performance for the epoxidation reaction of styrene using O2 as the only oxidant (conversion rate: 96%; selectivity: 90%). Reaction conditions: 104 mg of styrene, 20 mg of hierarchical pore high entropy metal-nitrogen-doped carbon catalyst and 1 mL of N,N-dimethylformamide (DMF) are placed in a reactor and reacted at 140°C for 20 hours under an oxygen atmosphere. The product mixture (100 μL) was poured into 0.5 mL of deuterated chloroform, and the product (styrene oxide) yield was measured by 1 H-NMR detection.

[0050] Embodiment 2:

[0051] (1) In a ball mill, add 0.06 mol of 2-methylimidazole (4.93 g), 0.8 mmol of Ni(NO3)2·6H2O (0.23 g), 0.8 mmol of Fe(NO3)3·9H2O (0.32 g), 0.8 mmol of Co(NO3)2·6H2O (0.23 g), 0.8 mmol of Cu(NO3)2·3H2O (0.19 g), 0.8 mmol of Mn(NO3)2·4H2O (0.20 g), 0.8 mmol of Ce(NO3)3·6H2O (0.35 g), 0.012 mol of Zn(NO3)2·6H2O (3.57 g), and 1.5 g of SiO2 microspheres (particle size 300nm) and 30 grinding balls (diameter 0.5cm) were milled at a speed of 1000r / min for 3h, wherein the total mass of the reactants was 10.02g. Finally, the mixture was washed with ethanol for 3 times and dried in vacuum at 100℃ to obtain SiO2@high entropy ZIFs composite.

[0052] (2) The obtained SiO2@high entropy ZIFs composite was placed in a quartz boat and heated in a tube furnace at 5°C min -1 The temperature was raised from room temperature to 950°C for 3 hours, and then cooled naturally to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composites. The composites were soaked in 1 mol / L sodium hydroxide solution for 1 day, washed with ethanol 3 times, and dried in vacuum at 100°C to obtain hierarchical pore high entropy metal-nitrogen doped carbon.

[0053] Embodiment 3:

[0054] (1) Add 0.06 mol of 2-methylimidazole (4.93 g), 0.6 mmol of NiSO4 (0.09 g), 0.6 mmol of Fe2(SO4)3 (0.24 g), 0.6 mmol of CoSO4 (0.09 g), 0.6 mmol of CuSO4 (0.10 g), 0.6 mmol of Ce(SO4)2 (0.20 g), 0.012 mol of Zn(OH)2 (1.19 g), 1 g of SiO2 microspheres (particle size of 300 nm) and 25 grinding balls (diameter of 0.5 cm) into a ball mill and mill for 3 h at a speed of 1000 r / min. The total mass of the reactants is 6.84 g. Finally, wash the mixture with ethanol three times and dry it in vacuum at 80 °C to obtain the SiO2@high entropy ZIFs composite.

[0055] (2) The obtained SiO2@high entropy ZIFs composite was placed in a quartz boat and heated in a tube furnace at 5°C min -1 The temperature was raised from room temperature to 950°C for 3 hours, and then cooled naturally to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composites. The composites were soaked in 10% hydrofluoric acid for 1 day, washed with ethanol for 3 times, and dried in vacuum at 100°C to obtain hierarchical pore high entropy metal-nitrogen doped carbon.

[0056] Embodiment 4:

[0057] (1) In a ball mill, 0.24 mol of 2-methylimidazole (19.70 g), 1.2 mmol of Ni(CH3COO)2 (0.21 g), 1.2 mmol of Fe(OH)(CH3COO)2 (0.23 g), 1.2 mmol of Co(CH3COO)2 (0.21 g), 1.2 mmol of Cu(CH3COO)2·H2O (0.24 g), 1.2 mmol of Mn(CH3COO)2·4H2O (0.29 g), 1.2 mmol of CeCl3·H2O (0.32 g), 0.036 mol of Zn(NO3)2·6H2O (10.71 g), and 2 g of SiO2 microspheres (particle size 400nm) and 90 grinding balls (diameter 0.5cm) were milled at a speed of 1000r / min for 3h, wherein the total mass of the reactants was 31.91g. Finally, the mixture was washed with ethanol for 3 times and vacuum dried at 90℃ to obtain SiO2@high entropy ZIFs composite.

[0058] (2) The obtained SiO2@high entropy ZIFs composite was placed in a quartz boat and heated in a tube furnace at 5°C min -1The temperature was raised from room temperature to 1100°C for 3 hours, and then cooled naturally to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composites. The composites were soaked in 1 mol / L sodium hydroxide solution for 1 day, washed with ethanol 3 times, and dried in vacuum at 100°C to obtain hierarchical pore high entropy metal-nitrogen doped carbon.

[0059] Embodiment 5:

[0060] (1) 0.06 mol of 2-methylimidazole (4.93 g), 0.4 mmol of Ni(NO3)2·6H2O (0.12 g), 0.4 mmol of Fe(NO3)3 (0.10 g), 0.4 mmol of CoSO4 (0.06 g), 0.4 mmol of Cu(CH3COO)2·H2O (0.08 g), 0.4 mmol of MnSO4 (0.06 g), 0.4 mmol of CeCl3 (0.10 g), 0.012 mol of ZnO (0.98 g), 3 g of SiO2 microspheres (500 nm in diameter) and 30 grinding balls (0.5 cm in diameter) were added to a ball mill and milled at a speed of 1000 r / min for 3 h. The total mass of the reactants was 6.43 g. Finally, the mixture was washed with ethanol three times and dried in vacuum at 90 °C to obtain the SiO2@high entropy ZIFs composite.

[0061] (2) The obtained SiO2@high entropy ZIFs composite was placed in a quartz boat and heated in a tube furnace at 5°C min -1 The temperature was raised from room temperature to 1000°C for 3 hours, and then cooled naturally to room temperature to obtain SiO2@high entropy metal-nitrogen doped carbon composites. The composites were soaked in 1 mol / L sodium hydroxide solution for 1 day, washed with ethanol 3 times, and dried in vacuum at 100°C to obtain hierarchical pore high entropy metal-nitrogen doped carbon.

[0062] From the above examples, it can be seen that the present invention uses ball milling to prepare SiO2@high entropy ZIFs composites, and uses high-temperature pyrolysis and chemical etching to prepare hierarchical pore high entropy metal-nitrogen-doped carbon catalysts. The prepared material not only has a hierarchical pore (macroporous-microporous) structure, but also has multi-component high entropy metal single atoms, which makes it have huge potential application value. At the same time, the preparation process of this method is simple and easy to mass produce.

[0063] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a hierarchical pore high entropy metal-nitrogen doped carbon catalyst, characterized in that: The method comprises the following steps: 1) Preparation of SiO2@high entropy ZIFs composites by ball milling The reactants, SiO2 microspheres and grinding balls were placed in a ball mill for 1-10 h, and then washed and vacuum dried to obtain a SiO2@high entropy ZIFs composite. The reactants are 2-methylimidazole, a zinc-containing compound and a mixed metal salt; the mass of SiO2 microspheres corresponding to 1 g of the reactants is 0.05-5 g; the total molar amount of the mixed metal salt and the zinc-containing compound corresponding to 1 mol of 2-methylimidazole is 0.02-1 mol, and the molar ratio of the mixed metal salt to the zinc-containing compound is 1:1-20; The mixed metal salt is any five or all six metal salts of iron salt, cobalt salt, nickel salt, copper salt, manganese salt and cerium salt, and the molar ratio of each metal salt is 1:1; 2) Preparation of hierarchical pore high entropy metal-nitrogen doped carbon catalysts The SiO2@ high entropy ZIFs composite obtained in the previous step was placed in a quartz boat and heated in a tube furnace at 2-5 °C min -1 The temperature was raised from room temperature to 800-1100 °C and maintained for 1-3 h, then naturally cooled to room temperature, soaked in acid or alkali for 1-4 days, then washed with ethanol and vacuum dried to obtain a hierarchical pore high entropy metal-nitrogen doped carbon catalyst; The iron salt is: Fe(NO3)3·9H2O, Fe(NO3)3, Fe2(SO4)3 or Fe(OH)(CH3COO)2; Cobalt salts are: Co(NO3)2·6H2O, Co(NO3)2, CoSO4 or Co(CH3COO)2; Nickel salts are: Ni(NO3)2·6H2O, Ni(NO3)2, NiSO4 or Ni(CH3COO)2; Copper salts are: Cu(NO3)2·3H2O, Cu(NO3)2, CuSO4 or Cu(CH3COO)2·H2O; Manganese salts are: Mn(NO3)2·4H2O, Mn(NO3)2, MnSO4 or Mn(CH3COO)2·4H2O; Cerium salt is: Ce(NO3)3·6H2O, CeCl3, Ce(SO4)2 or CeCl3·H2O; The zinc-containing compound is Zn(OH)2, ZnO, Zn(NO3)2·6H2O or Zn(NO3)2; The particle size of the SiO2 microspheres is 100-1000 nm.

2. The method for preparing the hierarchical pore high entropy metal-nitrogen doped carbon catalyst according to claim 1, characterized in that: The diameter of the grinding balls is 0.4 cm to 1.0 cm; the number of grinding balls corresponding to 1 g of reactant is 2 to 30; and the speed of the ball mill is 300-3000 r / min.

3. The method for preparing the hierarchical pore high entropy metal-nitrogen doped carbon catalyst according to claim 1, characterized in that: The temperature of vacuum drying in steps (1) and (2) is 70-100°C.

4. The method for preparing the hierarchical pore high entropy metal-nitrogen doped carbon catalyst according to claim 1, characterized in that: The acid is hydrofluoric acid with a mass fraction of 10-40%, and the base is 0.5 mol / L-2 mol / L sodium hydroxide solution.

Citation Information

Patent Citations

  • Nitrogen-doped carbon material supported alloy catalyst as well as preparation method and application thereof

    CN111054416A

  • Preparation method of monatomic catalyst, and prepared product and application thereof

    CN112206802A

  • Preparation method of bamboo-like nitrogen-doped carbon nanotubes loaded with metal monoatoms and nanoparticles

    CN113786856A